Practical action : Wittgenstein, pragmatism and sociology - Ogien, Albert (Cambridge Scholars Publishing, 2018)
This book delineates a pluralist and dynamic model of practical action which thoughtfully takes into account the reflexive conception of agency that is, by and large, prevailing in current social sciences research. Such a model will challenge the one the cognitive sciences have rather successfully imposed on our understanding of the relationship between knowledge and action. To make this model available, the book compares Wittgenstein's theses on knowing, the pragmatist outlook on inquiry and the analysis of action in common offered by interactionist sociology. It thus shows how an integrated.